Neonates in the Intensive Care Unit: Maternal Health-Related Quality of Life and Depression After Term and Preterm Births - Mautner, Eva; Stern, Christina; Avian, Alexander; Deutsch, Maria; Schöll, Wolfgang; Greimel, Elfriede (Frontiers in Pediatrics, 2022)
Background/Objective: To examine maternal physical and mental health-related quality of life (HRQoL) and depression after early and late preterm and term births in the early postpartum period. Method: In a prospective pilot study, three groups of women whose newborns had to be treated in the neonatal ward during the immediate postpartum period were established and compared with each other: 20 women with extremely to very preterm birth, 20 with moderate to late preterm birth and 20 women with term birth. All participants completed the Short Form-12 Health Survey (SF-12) to measure HRQoL, and the Edinburgh Postnatal Depression Scale (EPDS) to detect depressive symptoms combined with independently developed questions to evaluate anxiety and psychological distress. Results: Maternal psychological HRQoL was significantly worse in the very preterm birth group compared to moderate to late preterm birth (p < 0.001) and full-term birth groups (p = 0.004). There were no differences between the birth groups in depressive symptoms (p = 0.083), anxiety (p = 0.238), perceived stress (p = 0.340) and the general psychological distress values (p = 0.755). In the EPDS, the depression screening instrument 30 to 65% were beyond the cut-off-value to detect major depression. Conclusions: During the early postpartum period, an extensive medical care focussing on acute stress, HRQoL parameters and depression may be a good step to improving maternal well-being.